A study on the perception of male librarians and library paraprofessionals of the University of the Philippines and Rizal Library of Ateneo de Manila University on librarianship as their profession in relation to their gender - Macalanda, Angelie Mae D.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Librarianship as a profession derives its specific tasks and responsibilities from standards such as Republic Act 9246 or the Philippine Librarianship act, the Librarians' Code of Ethics and is regulated through the Licensure Examination. In this regard, written codes describe their roles; on the other hand, their patrons, colleagues and the library environment from in the workplace prescribe patterns on how they do their work. Therefore, the definition of a librarian's role goes beyond what is written in the codes, and is contextualized in the library environment where he/she belongs. Employing a greater number of women than men, librarianship is labeled as a "feminized profession," wherein it is usually described to be related to nursing and childcare, wherein men are considered a minority and are argued to be endowed with specific roles apart from the librarian in general.
It is in these representations that this study sought sights on what librarians and librarianship are (particularly a male one), what are the librarians' roles and characteristics, and professional identity, all on the basis of their self-perceptions on their performance at their workplace. Male librarians and library paraprofessionals from two academic institutions namely, the Rizal Library, Ateneo de Manila University and 6 library units from the University of the Philippines, Diliman were subjects of the study.
A total of 11 male librarians/library paraprofessionals from Rizal Library and 42 from UP served as respondents of the study. The number of respondents was identified through the list of staff requested from the Administrative Section of each library. The structured questionnaire that was administered included questions adopted from RA 9246 and from studies of Foit & Kittle (2002) and Piper & Collamer (2001). Each statement in the questionnaire served as variables for the study, to find out the relationship between the perceived roles and characteristics of a male librarian/library paraprofessional and their professional identity. Correlation is the statistical method utilized for data analysis and interpretation.
The data gathered from the questionnaires revealed that male librarians/library paraprofessionals perceive: (a)gender-based differences in their roles, but not on characteristics and professional identity, (b)a librarian/library paraprofessional as an information provider, a professional, and a well-organized individual; (c)maintenance and stewardship of the library and its materials as the most appropriate aspect of librarianship for them; (d) the roles of a librarian and library paraprofessional in general are similar with what the roles prescribed to male librarians; however, binding books, repair, maintenance, delivery, relocation and operation of materials are the roles which stood out to be prescribed to male librarians/paraprofessionals; (e)Information Science, computers and technology as aspects in librarianship they are most interested in; (f)being left out not because of gender or number, but because of age, years in service, and skills that are not suitable to any aspect of librarianship; and (g) Librarianship as an emerging field with emerging roles and number of male librarians.
Recommendations include conducting a follow-up study that delves on the librarian's interest in information science, and their perceptions on it as an emerging aspect of librarianship. Studying female and public librarians can also be made.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman Libraries; Ateneo de Manila University Rizal Library; Librarians -- Psychology; Library technicians -- Philippines